Mechanical properties of an additive manufactured CF-PLA/ABS hybrid composite sheet - Ahmed, S.W. (SAGE Publications Ltd, 2021)
Laminar composites have widespread applications in the automotive and aircraft industry. This research was aimed to investigate the suitability of fused deposition modeling to produce multi-material laminar composites. Composites comprising of two dissimilar laminates, named as hybrid composites, were printed from acrylonitrile butadiene styrene filament and carbon fiber-reinforced polylactic acid filament (a composite filament) by varying different printing parameters. Tensile tests were conducted to examine the mechanical performance of the produced composite sheet. A detailed analysis of the results revealed that a high ultimate tensile strength is primarily achieved by setting low values of printing speed, layer height, and clad ratio while high elongation is obtained by employing low printing speed, medium layer height, and high clad ratio. The optimum printing conditions were sought out through desirability function with an objective to simultaneously enhance all the considered properties. Further, the composite sheet exhibited a reasonably good combination of tensile properties as compared to its monolithic constituent sheets. Based on the results, it is concluded that the bi-material laminating approach employed herein can produce printed structures with desired properties. Â© The Author(s) 2019.